Analysis of Voltage Drop and Power Losses on Medium Voltage 20 KV Distribution System Kotamobagu Area Supplied from PLTD Kotamobagu - Yuslizar E.P. Bachari; Yasin Mohamad; Taufiq Ismail Yusuf; Lanto Mohamad Kamil Amali (JEECS (Journal of Electrical Engineering and Computer Sciences), 2024)
Drop voltage and power loss at the distribution system of electricity power in the Kotamobagu Area are caused by several factors, a namely far distance of a place that is distributed by electricity power from the source, imbalance load, equipment age, the diameter of the conductor, a distance of powerhouse to the consumer is too far and connection point are caused for technical loss. If it keeps happening, it will decrease the reliability of the electric power system and the distributed quality of the electricity power as well as it can damage the equipment. Therefore, unbalanced loading should be decreased at the phase, and overloading at the network will cause PT PLN (Persero) loss in the Kotamobagu Area. This research aims to analyze voltage drop, percentage of voltage drop, and power loss at every medium voltage feeder of 20 KV that is supplied from PLTD (Steam Power Plant) Kotamobagu until every transformer of distribution at peak load. After it is analyzed, the feeder OK 1, OK 2, OK 3, OK 4, OK 5 obtain the most significant value of drop voltage for 7.221 KV, 1.94 KV, 6.472 KV, 5.04 KV, 4.878 KV, respectively, with a percentage value of 56.507%, 10.742%, 47.841%, 33.689 %,32.257%. All OK happen at powerhouse K-153 (Kobo Besar), K-158 (RS. Monompia Kotamobagu), K-187 (Poopo I), K-201 (Motoboi Kecil), K-287 (Moyag I), respectively. The most significant power loss of 11.890 KW, 4.820 KW, 9.819 KW, 7.311 KW, 10.533 KW happen at powerhouse K-140 (Matali I), K-158 (RS. Monompia Kotamobagu), K-167 (Bilalang V), K-201 (Motoboi Kecil) and K-287 (Moyag I), respectively.